A prospective cross‐sectional study of anxiety and depression in patients with psoriasis in Singapore. (30th March 2016) - Tee, S.I.; Lim, Z.V.; Theng, C.T.; Chan, K.L.; Giam, Y.C.
Abstract: Background: Psoriasis has a negative psychological impact on patients, and may have repercussions on treatment outcomes. Despite this, the degree to which psoriatic patients suffer from psychiatric disorders has not received much attention in Singapore. Objective: This prospective cross‐sectional study was conducted to determine the frequency of anxiety and depression in a cohort of Singaporean patients with psoriasis, and explore its relationship with regards to physical disease severity and subjective quality of life. Methods: 100 patients aged 21–60 years old who visited the National Skin Centre, Singapore from 2008 to 2009 were enrolled into the study. Anxiety and depression were quantified using the Hospital Anxiety and Depression Scale (HADS). Disease severity was quantified with the Psoriasis Area Severity Index (PASI) and quality of life measured with the Short Form (36) Health Survey (SF‐36). Results: Using the HADS, the mean score for anxiety was 6.9 and that for depression was 4.7. An anxiety disorder was suggested in 17%, while a depressive disorder was suggested in 15% of the study population. All eight domains of the SF‐36 were significantly correlated with both anxiety and depression scores. Patients with moderate or severe psoriasis (on PASI) had worse depression scores than those with mild psoriasis. No association was found between anxiety scores and PASI. Neither was any significant correlation seen between anxiety and depression scores vs. patients' age, monthly income and duration of psoriasis. Conclusion: This study demonstrates the strong psychiatric morbidity in patients with psoriasis, for which further psychiatric evaluation should be considered.